Analysis of The Effect of Changes in Biological Education Student Routine During Covid-19 Pandemic on Learning Spirit and Understanding Lecture Materials - Iwan Ridwan Yusup; Sumiyati Sa'adah; Milla Listiawati; Idad Suhada (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
Online and offline learning will have a different impact on the level of understanding of students about learning materials. In this study the researchers tried to find out how the learning activities of Biology Education students at UIN Sunan Gunung Djati Bandung during the pandemic were related to changes in routine during the pandemic which affected the enthusiasm for learning and understanding of lecture material during the pandemic compared to before the pandemic. This research uses descriptive research method because in its implementation it includes data, analysis and interpretation of the meaning and data obtained. This study uses a questionnaire, the list of questions is structured in the form of multiple-choice questions and open questions (multiple choice questions and open questions). This method is used to obtain data about the effect of changes in the routine of Biology Education students during the pandemic on learning enthusiasm and understanding the material from respondents. Biology education students admit that there have been significant changes in their routine during the pandemic period. These changes have an impact on student learning activities.